2020
DOI: 10.1108/ecam-09-2019-0518
|View full text |Cite
|
Sign up to set email alerts
|

A field survey of hand–arm vibration exposure in the UK utilities sector

Abstract: PurposeExcessive exposure to HAV can lead to hand–arm vibration syndrome (HAVS) which is a major health and well-being issue that can irreparably damage the neurological, vascular and muscular skeletal system. This paper reports upon field research analysis of the hand–arm vibration (HAV) exposure levels of utility workers in the UK construction sector when operating hand-held vibrating power tools.Design/methodology/approachAn empirical epistemological lens was adopted to analyse primary quantitative data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…This research adopted positivism analysis to conduct an empirical analysis of primary data collated from a questionnaire survey; such an approach is well established within contemporary construction management literature [73,74]. Positivism was first adopted to analyse extant literature and identify pertinent BIM implementation drivers in BIM awareness across the PL (i.e., model constructs and constructs classification) and build a conceptual model [75][76][77].…”
Section: Methodsmentioning
confidence: 99%
“…This research adopted positivism analysis to conduct an empirical analysis of primary data collated from a questionnaire survey; such an approach is well established within contemporary construction management literature [73,74]. Positivism was first adopted to analyse extant literature and identify pertinent BIM implementation drivers in BIM awareness across the PL (i.e., model constructs and constructs classification) and build a conceptual model [75][76][77].…”
Section: Methodsmentioning
confidence: 99%
“…The study adopts a post-positivism philosophical stance (Roberts et al, 2018;Al-Saeed et al, 2020), using a deductive approach (cf. Edwards et al, 2019;Edwards et al, 2020) since the study sought to identify and assess the challenges of smart city development. A survey strategy of enquiry was conducted using a structured questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…(Sui et al, 2018). H&S is especially important in the construction sector where the handling and manipulation of plant and machinery expose workers to serious or fatal injury ( al., 2003;Edwards et al, 2019;Edwards et al, 2020). For example, the UK government's Health and Safety Executive (HSE) found that of the five major categories of fatality occurring throughout industry during the period 2014/15 to 2018/19, stuck by moving vehicle and contact with moving machinery were responsible for 19% and 8% of all fatalities respectively (cf.…”
Section: Review No 2 Commentsmentioning
confidence: 99%
“…However, Edwards et al (2020) noted that whilst the measurement of HAV is precise, the risk of being over exposed, contracting HAVS and directly associating these with occupational activities if far from an exact science. A person's life-style must also be taken into consideration because social activities (for example, gardening) can over-expose humans to vibratory work processes (e.g.…”
Section: Hand-arm Vibration: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation